PENERAPAN KONSEP TRI N “NITENI, NIROKAKE, NAMBAHI’’ DALAM STRATEGY PEMASARAN DIGITAL PADA UMKM CV SAVITA INDONESIA - Paryanto, Alfin Dwi; Garnita, Ria; Lindawati, Lindawati; Septiani, Rizka Ayu; Aldo, Ketut; Reo, Petrus Renol; Purnamarini, Tri Ratna (Yayasan Education and Social Center, 2024)
This community service aims to provide in-depth understanding and share experiences regarding the application of Tamansiswa teachings, especially the Tri N concept: